Adaptive integral feedback controller for pitch and yaw channels of an AUV with actuator saturations. (November 2016) - Sarhadi, Pouria; Noei, Abolfazl Ranjbar; Khosravi, Alireza
Abstract: Input saturations and uncertain dynamics are among the practical challenges in control of autonomous vehicles. Adaptive control is known as a proper method to deal with the uncertain dynamics of these systems. Therefore, incorporating the ability to confront with input saturation in adaptive controllers can be valuable. In this paper, an adaptive autopilot is presented for the pitch and yaw channels of an autonomous underwater vehicle (AUV) in the presence of input saturations. This will be performed by combination of a model reference adaptive control (MRAC) with integral state feedback with a modern anti-windup (AW) compensator. MRAC with integral state feedback is commonly used in autonomous vehicles. However, some proper modifications need to be taken into account in order to cope with the saturation problem. To this end, a Riccati-based anti-windup (AW) compensator is employed. The presented technique is applied to the non-linear six degrees of freedom (DOF) model of an AUV and the obtained results are compared with that of its baseline method. Several simulation scenarios are executed in the pitch and yaw channels to evaluate the controller performance. Moreover, effectiveness of proposed adaptive controller is comprehensively investigated by implementing Monte Carlo simulations. The obtained results verify the performance of proposed method. Highlights: Adaptive pitch and yaw autopilots for input saturated AUVs are presented. Model reference adaptive control with augmented anti-windup compensated is proposed. The proposed method is applied to a six degrees of freedom model of REMUS AUV. Performance of the method is assessed by utilizing valuable Monte Carlo simulations.